2010
DOI: 10.1007/s12350-010-9248-9
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate response during vasodilator stress myocardial perfusion imaging: Mechanisms and implications

Abstract: See related article, pp. 617-624Myocardial perfusion imaging (MPI) using adenosine, dipyridamole, or regadenoson (a selective A 2A receptor agonist) is an established method for detecting coronary artery disease (CAD) and risk stratification. 1 In high-risk populations, as in those with diabetes mellitus (DM) or chronic kidney disease, MPI has been shown to be a powerful predictor of risk, but nevertheless, patients with normal myocardial perfusion are at higher risk than those without DM or chronic kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…25 Another interesting distinction is revealed by the study of Aljaroudi et al 8 In this study population that consisted exclusively of ESRD patients, the median and the quartiles of HRR were identical to the previously published distribution of HRR in 1156 consecutive …”
Section: Will This Novel Predictor Add Value To the Information That supporting
confidence: 77%
“…25 Another interesting distinction is revealed by the study of Aljaroudi et al 8 In this study population that consisted exclusively of ESRD patients, the median and the quartiles of HRR were identical to the previously published distribution of HRR in 1156 consecutive …”
Section: Will This Novel Predictor Add Value To the Information That supporting
confidence: 77%
“…23 We have previously noted that the HRR response to the clinically available agonists of the various A 2A receptor agonists is variable. 13 For example, regadenoson induces a higher HRR response than adenosine. 5,6 In a recent study, we defined a blunted HRR to adenosine as \10% (20% of the population) while in this study the lowest quartile had a HRR \17%.…”
Section: Predictors Of the Heart Rate Response To Regadenosonmentioning
confidence: 99%
“…[7][8][9][10][11][12] Since regadenoson induces a more intense increase in heart rate than adenosine, the prognostic information derived from adenosine studies can not be automatically applied to regadenoson. 5,6,13 This is the first study that examines the predictors and the prognostic value of the HRR to regadenoson with the hypothesis that the HRR carries incremental prognostic information to that derived from the perfusion pattern and the left ventricular (LV) ejection fraction (EF).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that diabetes, metabolic syndrome, and renal dysfunction were independent predictors of blunted heart rate response to adenosine or regadenoson with the HR response being dissociated from BP response. 14 More specifically, in the study by Hage et al, 15 the HR response decreased by 0.7%/10 mL/min/1.73 m 2 decline in eGFR. This blunted heart rate response to pharmacologic vasodilators seems to carry adverse prognostic value and needs further evaluation with autonomic function studies.…”
Section: Discussionmentioning
confidence: 93%